Decisions of the trial and appellate courts (Supreme Court Library of Korea, 2011)
Foreword to volume 1: "Volume I contains the English version of 29 decisons and orders made by the first and second instance courts from the year 2004 to 2010, for cases which reflect globally shared legal standards, cases which attracted high attention and interest domestically or internationally, and cases which deserve international attention for introducing aspects distinctive to the Korean legal system and culture."